Primary seminal vesicle diffuse large B-cell lymphoma: a case report and review of the literatures - Li, Youli; Cao, Sufen; Lv, Fangfang; Chen, Guang-Liang (Frontiers in Immunology, 2024)
Primary seminal vesicle lymphoma is a remarkably rare condition, predominantly manifesting as diffuse large B-cell lymphoma. Due to its rarity and nonspecific clinical presentations, it is often misdiagnosed or overlooked. Here, we report a case of a 68-year-old male diagnosed with primary seminal vesicle lymphoma, coinciding with prostate cancer. The diagnosis followed initial findings of elevated prostate-specific antigen levels and abnormal magnetic resonance imaging of the prostate and left seminal vesicle. Suspicion of prostate cancer led to a radical resection of both the prostate and seminal vesicle. Subsequent pathological examination and next-generation sequencing post-surgery confirmed the diagnosis of primary seminal vesicle diffuse large B-cell lymphoma, characterized by MYD88 L265P and CD79B double mutations type (MCD type).The patient was treated with six cycles of the R-CHOP regimen (rituximab, cyclophosphamide, vincristine, doxorubicin, prednisone), achieving complete metabolic remission as confirmed by positron emission tomography-computed tomography. Fifteen months post-treatment, the patient's condition remains favorable.Through our literature review of additional six cases of primary seminal vesicle lymphoma, we aim to elucidate the typical clinical presentations, imaging features, pathological characteristics, genetic mutations, and therapeutic strategies, aiming to contribute to better detection and management of this rare malignancy. This case underscores the diagnostic challenges and emphasizes the necessity for heightened clinical suspicion and definitive pathological examination in the management of primary seminal vesicle lymphoma.